The concept of european citizenship with regard to identity of the european union - Çelik, Deniz (My University, 2008)
Avrupa bütünleşmesinde kültür ve kimliğin yeri sorunsalı, bütünleşmenin bir adım daha ileri gidebilmesi için Avrupa’nın çözmesi gereken temel çıkmazlardan biridir. Bu çıkmaz, 2005 yılında Anayasal Antlaşma’nın onaylanması sürecinde yapılan referandumlarda Fransız ve Hollandalı seçmenlerce reddedilmesi ve Anayasal Antlaşma’nın yerine hazırlanan Lizbon Antlaşması’nın Temmuz 2008’de İrlanda referandumunda başarısızlığa uğramasıyla, daha açık ve önemli hale gelmiştir. Avrupa Birliği’nin çözmek zorunda olduğu bu kriz, Birlik’in vatandaşlarının nezdindeki meşruiyeti ve “daha yakın bir Birlik”in nasıl kurulacağı hakkındaki tartışmaları alevlendirmiştir. Bu çalışma, bir yönetim şekli olan Avrupa Birliği’ne ait olma duygusu üzerine oturan bir vatandaşlık bilinci ve Avrupa Birliği vatandaşlarının birlikte izleyebilecekleri belirli değerler ve siyasi hedefler sağlayabilecek politik bir Avrupa Birliği kimliğini tartışmaktadır.

The place of the culture and identity in the integration has long been one of the most basic challenges that the European integration has to solve for moving a step forward. This challenge became more apparent and crucial as a consequence of not only the rejection of the Constitutional Treaty by French and Dutch voters at the referenda hold for ratification in 2005, but also failure of the Treaty of Lisbon, which was prepared instead of the Constitution, at the Irish referendum in June 2008. This crisis that the European Union has to cope with has exacerbated the discussions about the legitimacy of the European Union in the eyes for its citizens and how ‘ever closer Union’ can be established. This study, in general, tries to discuss the possibility of a political identity of the European Union, which may establish a consciousness of citizens as a sense of belonging to the European Union as a polity and certain basic values and political objectives that citizens of the European Union pursue jointly.
Keywords: Avrupa Birliği; Avrupa Birliği_Kimlik; Siyaset ve Yönetim_Avrupa Birliği